HA-based dermal filler: downstream process comparison, impurity quantitation by validated HPLC-MS analysis, and in vivo residence time study. Issue 3 (July 2019) - Guarise, Cristian; Barbera, Carlo; Pavan, Mauro; Panfilo, Susi; Beninatto, Riccardo; Galesso, Devis
The success of hyaluronic acid (HA)-based dermal fillers, with more than 2 million minimally invasive procedures conducted in 2016 in the US alone, is due to their hygroscopic properties of biocompatibility and reversibility. The type and density of HA cross-linkage, as well as the manufacturing technology, may influence not only the in vivo persistence but also the safety profile of dermal fillers. 1, 4-Butanediol diglycidyl ether (BDDE) is the cross-linker used in most market-leading HA fillers; 1, 4-butanediol di-(propan-2, 3-diolyl) ether (BDPE) is the major impurity obtained from the HA–BDDE cross-linking (HBC) process. In this work, a new process to obtain high purity HBC fillers was developed. A new HPLC-MS method was validated for the quantification of BDPE content in HBC dermal fillers. In vitro cytotoxicity of BDPE was evaluated in fibroblasts (IC50 = 0.48 mg/mL). The viscoelasticity was monitored during the shelf-life of the HBC-10% hydrogel and was correlated with in vitro hyaluronidase resistance and in vivo residence time in a rabbit model. This analysis showed that elasticity is the best parameter to predict the in vivo residence time. Finally, a series of parameters were investigated in certain marketed dermal fillers and were compared with the results of the HBC-10% hydrogel.